FOREIGN IMMIGRATION IN THE MOLISE REGION OVER THE LAST DECADE. - Cristiano Pesaresi (Bollettino della Società Geografica Italiana)
Between 1951 and 2011 the population of Molise went from the all-time high of 406,823 inhabitants to its all-time low of 313,660 inhabitants (-22.9%). A number of studies have highlighted the conditions of socio-demographic hardships in which many municipalities find themselves, focussing the attention on the mountain areas and reasserting concerns expressed decades ago. Thus the contraction of the last decade has led to the use of the term «demographic drop», with a reflection on the future scenarios from which further declines are expected. The negative dynamics of 2001-2011 was worsened by the natural balance, conditioned by the marked ageing of the population, while the net migration balance showed positive values, thanks to the contribution of the international component. Therefore, there is the need to carry out interventions that make it possible to: check the movements towards other Italian contexts; attract a considerable amount of skilled labour from other regions; increase the number of foreign immigrants. In this way the migration balance would be bolstered and the conditions would be created for a rebalancing of the natural balance. Moreover, even the economicproduction system shows clear signs of imbalance, with few relatively strong links surrounded by many small coordinated municipalities that remain in an uncertain state of waiting. Since the migration balance due to the international component is at present the only active variable within the population movement, this paper gives an overall picture of the foreign immigration on a regional scale, highlighting the recent variations and comparing the situation of the Molise region with that of the general Italian context. The municipalities with the greatest number of foreigners are then examined. Interventions are envisaged so as to contribute to generating positive and non negligible effects.